Autonomous cooperative guidance based on distributed consensus and self-management. (November 2021) - Zhu, Jianwen; Su, Daliang; Sun, Haifeng; Tang, Ziao
As for the time-space cooperative guidance under complex offense–defense game conditions, this article proposes a distributed time-space cooperative guidance strategy based on consensus theory and missile group (MG) self-management. The strategy consists of a three-layer cooperative guidance system: the lower layer is the impact time and angle control guidance (ITACG) based on optimal control with minimum energy consumption. The middle layer is the time-space cooperative control strategy via distributed consistency with the time-to-go as the coordination variable. The upper layer is the MG self-management strategy considering the complex attack–defense conditions. The simulation results show that the cooperative strategy can achieve simultaneous attack at different directions and improve the penetration probability and the ability to respond to the attack–defense situation effectively.